Intraperitoneal oil application causes local inflammation with depletion of resident peritoneal macrophages - Alsina Sanchis, Elisenda; Mülfarth, Ronja; Moll, Iris; Mogler, Carolin; Rodriguez-Vita, Juan; Fischer, Andreas (Molecular cancer research, 2021)
Oil is frequently used as a solvent to inject lipophilic substances into the peritoneum of laboratory animals. Although mineral oil causes chronic peritoneal inflammation, little is known whether other oils are better suited. We show that olive, peanut, corn, or mineral oil causes xanthogranulomatous inflammation with depletion of resident peritoneal macrophages. However, there were striking differences in the severity of the inflammatory response. Peanut and mineral oil caused severe chronic inflammation with persistent neutrophil and monocyte recruitment, expansion of the vasculature, and fibrosis. Corn and olive oil provoked no or only mild signs of chronic inflammation. Mechanistically, the vegetal oils were taken up by macrophages leading to foam cell formation and induction of cell death. Olive oil triggered caspase-3 cleavage and apoptosis, which facilitate the resolution of inflammation. Peanut oil and, to a lesser degree, corn oil, triggered caspase-1 activation and macrophage pyroptosis, which impair the resolution of inflammation. As such, intraperitoneal oil administration can interfere with the outcome of subsequent experiments. As a proof of principle, intraperitoneal peanut oil injection was compared with its oral delivery in a thioglycolate-induced peritonitis model. The chronic peritoneal inflammation due to peanut oil injection impeded the proper recruitment of macrophages and the resolution of inflammation in this peritonitis model. In summary, the data indicate that it is advisable to deliver lipophilic substances, like tamoxifen, by oral gavage instead of intraperitoneal injection. - Implications: This work contributes to the reproducibility of animal research by helping to understand some of the undesired effects observed in animal experiments.
Published online first: November 2, 2020
Gesehen am 06.04.2021